A preliminary trial of the sedation induced by intranasal administration of midazolam alone or in combination with dexmedetomidine and reversal by atipamezole for a short-term immobilization in pigeons. (March 2015) - Hornak, Slavomir; Liptak, Tomas; Ledecky, Valent; Hromada, Rudolf; Bilek, Jan; Mazensky, David; Petrovic, Vladimir
Abstract: Objective: To assess the sedative and immobilization effect of intranasal administration (INS) of midazolam (MID) without or with INS dexmedetomidine (DXM), and some physiological changes induced by the drugs. The ability of INS atipamezole to reverse the DXM component was also assessed. Study design: Prospective 'blinded' experimental study. Animals: In total, 15 pigeons. Methods: Pigeons were sedated by INS MID alone at a dose of 5 mg kg −1 (group MID, n = 6) or in combination with INS DXM at a dose 80 μg kg −1 (group MID-DXM, n = 6). Measurements were made of heart rate (HR), respiratory rate ( f R ) and cloacal temperature (CT). The degree of sedation was assessed at 15 minutes prior to, immediately after, and at intervals until 100 minutes after drug administrations. Following MID-DXM, INS atipamezole (250 μg kg −1 ) was administered and the same indices measured 5 and 10 minutes later. Results: MID had no effect on HR and f R, and although CT decreased, it remained within physiological range. MID-DXM caused significant falls in HR, f R and CT that persisted until the end of sedation. Atipamezole antagonized sedation and cardiorespiratory side effects of MID-DXM within 10 minutes of application. In addition, for MID compared to MID-DXM, the lowest sedation scores [10 (7–14) and 10.5 (5–14) versus 2 (1–4) and 2 (1–5)] were achieved in the 10th and 20th minute versus the 20th and 30th minute of the sedation, respectively. Conclusions and clinical relevance: MID alone, given INS had minimal side effects on vital functions but caused inadequate immobilization of pigeons for restraint in dorsal recumbency. MID - DXM caused an effective degree of immobilization from 20 to 30 minutes after administration, at which time birds tolerated postural changes without resistance. Atipamezole antagonized both side effects and sedation, but complete recovery had not occurred within 10 minutes after its application.